THE EFFECT OF USING BOARD GAME ON STUDENTS’ VOCABULARY MASTERY - Rupiah Sari (JURNAL LINER (Language Intelligence and Educational Research), 2019)
Abstract: The aims of this research are to know: 1) The extent of the application of using Board Game in teaching vocabulary at the eighth grade students of SMP Negeri 2 Saipar Dolok Hole, 2) The extent of the students’ vocabulary mastery before and after taught by using Board Game at the eighth grade students of SMP Negeri 2 Saipar Dolok Hole, 3) Whether any significant effect of Board Game on students’ vocabulary mastery at the eighth grade students of SMP Negeri 2 Saipar Dolok Hole . The population of this research is all of the eighth grade students of SMP Negeri 2 Saipar Dolok Hole which consist of 119 students. Sample were 30 students which taken by using systematic sampling. The research method that used was experimental method. To collect the data the writer used observation sheet and test as an instrument. The mean score of the application of Board Game was 3.3, it was categorized “Very good”. The result of data analysis shows that ttest=17,04 while ttable=2.04. it means that ttest is higher than ttable. So, the hypothesis is accepted. It means that there is significant effect of Board Game on students’ vocabulary mastery at the eighth grade students SMP Negeri 2 Saipar Dolok Hole.